Bilingual identities in two UK communities: a study of the languages and literacies of Welsh and British-Asian girls - Jones, Susan Mary (2009)
This thesis considers the role of language and literacy in supporting the exploration of bilingual identities. Two groups of bilingual girls participated in the study when they were aged between 11 and 13. One group are British-Asian girls, located within an English inner-city; the other group live in North West Wales.